Cell reactions of inflammation focus in carrageenan secondary chronic inflammation on the background of substance P blockade - O. M. Shevchenko; V. O. Sych (Kazimierz Wielki University, 2020)
The aim of the study was to determine the features of cellular reactions of the inflammatory focus in carrageenan secondary chronic inflammation against the background of blockade of substance P. Experimental prospective controlled randomized study was performed on 132 WAG rats in series of 6 animals in each series: in control and for 6 hours; 1, 2, 3, 5, 7, 10, 14, 21, 28 days in the conditions of the natural course of carrageenan inflammation and with the use of a pharmacological preparation, aprepitant - an inhibitor of NK-1 receptors. During the observation period of 6 hours to 3 days, neutrophilic, basophilic and eosinophilic leukocytes accumulate (phase of exudation of the inflammatory process). Peaks of neutrophils and basophils occur on day 2 (neutrophils - in the central parts of the inflammatory focus, basophils - in both areas, in the center and on the periphery) with a small predominance of the number of cells in the peripheral parts. The peak number of eosinophils occurs on day 1 and with a slight decrease on day 2 with their predominant location in peripheral areas. From 3-5 days the cellular composition of the infiltrate was characterized by a predominance of lymphocytes, monocytes, macrophages, plasma cells, tissue basophils, cells of the fibroblastic series, which during blockade of substance P in a single amount appear for 2 days, predominate in peripheral areas (phases of proliferation and organization).